Nursing Interventions in stem cell therapy for cardiovascular diseases: A Systematic Review - Thapar, Lovely; Mandal, Riya; Qadir, Harshna Richard (Journal of Neonatal Surgery, 2025)
Background: cardiovascular diseases (CVDs) remain the leading cause of mortality globally. Stem cell therapy has emerged as a promising treatment modality, and nurses play a critical role in the care continuum, from patient preparation to post-therapy monitoring. This systematic review aims to synthesize the existing evidence on nursing interventions supporting stem cell therapy and outcomes in CVDs. Methods: A systematic search was conducted across PubMed, CINAHL, Scopus, and Cochrane Library databases for studies published between 2013 and 2024. The inclusion criteria focused on peer- reviewed studies reporting nursing-led or nursing-related interventions in adult patients undergoing stem cell therapy for cardiovascular conditions. Quality appraisal was performed using the Joanna Briggs Institute Critical Appraisal tools. Results: Six studies met the inclusion criteria. Study 1 emphasized the importance of pre-therapy education, demonstrating that structured nurse-led counseling significantly improved patients' treatment adherence and reduced anxiety levels (p < 0.05). Study 2 explored infection prevention practices, revealing that standardized aseptic protocols administered by trained nurses lowered catheter-related bloodstream infections by 30%. Study 3 highlighted the role of nurses in the mobilization and collection of peripheral blood stem cells, where a nurse- coordinated care model improved stem cell yield and patient satisfaction scores. Study 4 investigated post-transplant cardiac monitoring, finding that nurse-implemented telemetry surveillance facilitated early detection of arrhythmias in 92% of patients. Study 5 evaluated symptom management, showing that tailored nursing interventions reduced fatigue and dyspnea scores during recovery. Lastly, Study 6 reported that continuity of care through nurse- led follow-up clinics significantly enhanced quality-of-life measures and reduced 90-day hospital readmission rates by 25%. Conclusion: Nursing interventions are pivotal in optimizing the delivery and effectiveness of stem cell therapy for cardiovascular diseases. From pre-treatment education to long-term follow-up, nurses contribute significantly to patient outcomes. Further research is needed to standardize these interventions and assess their cost-effectiveness across diverse clinical settings.